Call the Psychiatrist! - Study about Delirium in the context of liaison psychiatry. (1st June 2022) - Fonseca Vaz, I.; Mouta, S.; Jesus, B.; Castro, S.
Abstract : Introduction: Delirium is characterized as a short-term consciousness and cognition disturbance which tends to fluctuate during the course of the day. It is a common and serious problem, mainly in hospitalized older adults, potentially avoidable and often poorly recognized. Objectives: We propose an analysis on the theme through a work that evaluates the requests for psychiatric consultation made in a district hospital in Portugal during the course of 12 months. Methods: We identified all patients on the requests for psychiatric consultation and obtained a demographic, clinical and consultation requests by medical specialties data and conducted statistical analysis using Excel. Results: We identified 106 consultation requests, in which 41 cases were eventually diagnosed as delirium. Most (83%) were hyperactive delirium, 12% were hypoactive delirium and 5% were mixed delirium. Incidence was higher in males (59%) and in those aged between 66 and 80 years old (56.1%). Most consultation requests were made by Internal Medicine (46.3%), followed by General Surgery (26.8%), Pulmonology (14.6%), Orthopedics (9.8%) and Neurology (2.5%). Finally, we analyzed which symptoms mentioned in the request made physicians consider requesting a psychiatric evaluation. Approximately half of the cases (48.8%) reported psychomotor agitation, followed by temporal/spatial disorientation (41.5%) and aggressive behaviour (17.1%). Conclusions: We highlight a still notorious lack of proper identification of delirium, resulting in symptoms being incorrectly interpreted as a psychiatric disorder. This may cause a delay in the adequate diagnosis and management of the condition, increasing the morbidity and mortality of patients. Disclosure: No significant relationships.